CONGENITAL HYPOPITUITARISM PRESENTING DURING THE NEONATAL PERIOD: A CASE REPORT - Tan, Su Fang; Gan, Cheng Guang; Wong, Sl Jeanne; Selveindran, Nalini M; Hong, Janet Yh (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Congenital hypopituitarism may present as isolated or combined pituitary hormone deficiencies. The incidence reported is in between 1 in 4000 to 1 in 10,000. It may occur due to developmental defects of the pituitary gland or genetic mutations. Prompt recognition during infancy and appropriate replacements of hormone deficiencies are essential. However, the diagnosis can be challenging due to its variable presentation and non-specific symptoms. RESULTS The index case is a 2-year-old girl who presented with recurrent hypoglycemia and salt-losing crisis during the neonatal period. On examination, she has soft dysmorphism (widened sagittal sutures, down-slating palpebral fissure, high arch palate, flat nasal bridge). Critical sampling taken during the hypoglycemia episode (blood glucose 1.5 mmol/L) revealed extremely low serum cortisol (3.8 nmol/L) and growth hormone (0.02 mcg/L) levels. She also had central hypothyroidism characterized by a low free-thyroxine but inappropriately normal TSH (TSH 5.68 miU/L, FT4 7.12 pmol/L). She was started on hydrocortisone, L-thyroxine and daily subcutaneous recombinant growth hormone (GH) therapy. GH was started early for the hypoglycaemia. There was no clinical or biochemical picture of diabetes insipidus. Magnetic resonance imaging (MRI) of pituitary done at 10 months of age shows a hypoplastic pituitary gland with a normal infundibulum and absence of high signal changes in the posterior lobe of the gland. CONCLUSION Congenital hypopituitarism can be a life-threatening condition manifesting during the neonatal period with hypoglycaemia and salt-wasting crisis. Early diagnosis and treatment are essential.